Greece : Selected Issue-An Overview of Pension Reform. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issue paper provides an overview of the public pension system in Greece, and of prospective pension-related spending pressures. The paper reviews the structure of Greece's pension system and compares some basic parameters of the Greek pension system with those of other European Union economies. It provides an overview of demographic projections for Greece in an international context. The paper also examines the sensitivity of the expenditure projections to variations in demographic and macroeconomic assumptions, including those relating to the rate of productivity growth.